2021
DOI: 10.1111/aji.13395
|View full text |Cite
|
Sign up to set email alerts
|

A systemic review of intravenous immunoglobulin G treatment in women with recurrent implantation failures and recurrent pregnancy losses

Abstract: Over the last few decades, the advancement in reproductive technologies and protocols to improve embryo quality through culture techniques and genetic testing to eliminate chromosomally abnormal embryos resulted in better pregnancy rates and outcomes after fertility treatments. Unfortunately, some patients still struggle with recurrent implantation failures (RIFs) and recurrent pregnancy losses (RPLs). Immune etiologies have been attributed to play an important role in some of those patients. Maintaining a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“… 33 To summarize, most recent meta-analyses suggested that initiation of IVIG before conception, and treatment in women with abnormal immunity such as increased NK cell levels, could have a potentially beneficial effect on the live birth rate, although the evidence is still at level 2. 31 In our study, the live birth rate was high regardless of type of RPL, timing of IVIG, and presence of autoantibodies. However, our study population had more patients with primary RPL, who were treated after conception.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“… 33 To summarize, most recent meta-analyses suggested that initiation of IVIG before conception, and treatment in women with abnormal immunity such as increased NK cell levels, could have a potentially beneficial effect on the live birth rate, although the evidence is still at level 2. 31 In our study, the live birth rate was high regardless of type of RPL, timing of IVIG, and presence of autoantibodies. However, our study population had more patients with primary RPL, who were treated after conception.…”
Section: Discussionmentioning
confidence: 44%
“…The subgroup analyses vary from study to study, and due to heterogeneity of study populations, opinions on the efficacy of IVIG in recent meta-analyses are conflicting. 4 6 29 30 31 For example, Wang et al 29 concluded that IVIG may have potential benefits in the live birth rate in URPL, but evidence is insufficient (relative risk [RR], 1.25; 95% confidence interval [CI], 1.00–1.56; P = 0.05). However, subgroup analysis showed that the live birth rate marginally increased in secondary RPL (RR, 1.26; 95% CI, 0.99–1.60; P = 0.06), which is similar to that of the Egerup et al’s study, 32 and significantly increased in patients who received IVIG before conception (RR, 1.67; 95% CI, 1.3–2.14; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential cause for increased perivillous fibrin in both Ig-treated groups compared to the mock controls is direct injury to the syncytiotrophoblast from nonspecific antibody binding to the syncytiotrophoblast that could be activating complement. Interestingly, human IVIG is used to treat several disorders in pregnancy, and does not seem to lead to direct syncytiotrophoblast injury in those instances, suggesting that the nonspecific injury to the rhesus macaque villi may be a species-specific effect of the administration of human IgG [ 31 , 32 ]. There has been some evidence of increased fetal growth restriction and perhaps pre-term birth in a recently tested HIG product to prevent congenital CMV; therefore it is important to continue to assess safety of these products during pregnancy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular injury caused by high-dose IVIG has been reported 27 . A previous review recommended that patients with recurrent pregnancy loss should have liver function tests before using IVIG 28 . Our results clearly indicate that IVIG using in early pregnancy increased the risk of liver injury.…”
Section: Discussionmentioning
confidence: 99%